4CPS-398 Use of intravenous iron in heart failure octogenarians and nonagenarians with iron deficiency. (14th March 2021) - Fernandez, S; Ortonobes, S; Soler, N; Rovira, T; Florit, M; Redondo, S; Gomez, M
Abstract : Background and importance: Anaemia is an important comorbidity in heart failure (HF), and iron deficiency (ID) is the commonest contributing factor. Intravenous iron therapy improves quality of life although data in elderly patients are scarce. Aim and objectives: To describe the use of iron in patients with HF and ID and to analyse differences between receiving or not intravenous iron. Material and methods: A retrospective observational study was conducted in a university hospital. From January to March 2019, the acute geriatric unit admitted octogenarian and nonagenarian patients for unbalanced HF and ID. Registered variables were: sociodemographics, length of stay (LOS), Barthel Index, oral iron supplements, use of intravenous iron during admission, analytical parameters at admission and post-discharge, mortality and readmission at 6 months. Definitions: anaemia (haemoglobin: men <13.0 g/dL; women <12.0); ID (ferritin <100 μg/L or 100–299 with transferrin saturation (TSAT) <20%). Results: Among 89 unbalanced HF patients admitted, 38 were diagnosed with ID ( table 1 ). Conclusion and relevance: In our octogenarian and nonagenarian cohorts, 58% of patients received intravenous iron, higher than in similar studies. According to the guidelines, no oral iron was prescribed, neither during admission nor at discharge. Intravenous iron increased LOS, without affecting mortality. However, ID parameters improved. References and/or acknowledgements: Conflict of interest: No conflict of interest